GAME VISUAL NOVEL DENGAN METODE RAPID APPLICATION DEVELOPMENTENT (RAD) BERBASIS MOBILE LEARNING - Faisal, Faisal; Nopriadi, Nopriadi (Computer Science and Industrial Engineering, 2022)
Technology will change along with the times and affects all aspects, even in phrase of children there are more interested in interactive educational learning methods compared to conventional learning from books. in essence, kids easily interested when learning through media that visual by summarizing the game and learning knowledge. In educating children, the role of parents is very important, especially in this digital era. Less about study case seven wonder world in material make children's lack of knowledge of the outside world. This application makes by ren’py with the Python programming language and android smartphone base. The research method that is Rapid Application Development (RAD) technique with object-oriented approach and uses UML as a tool for media development. Library research methods and interview is data collecting method, design system is using Unified Modeling Language (UML). The result of research is application for introducing about seven wonder worlds. The result of this program research is more interested or attractive to children than textbooks. This application is expected to educate kids to know the wonders of the world with entertain and knowledge